2017
DOI: 10.1007/s10144-017-0581-6
|View full text |Cite
|
Sign up to set email alerts
|

The influence of time since introduction on the population growth of introduced species and the consequences for management

Abstract: Several processes likely act to change the demographic rates of introduced species over time, and this changing demography could influence the optimal management of invasive populations. Optimal management strategies should be derived based on the demography. However, we have a poor understanding of the degree to which the demography of introduced species changes following initial introduction. We used published matrix population models of introduced plant populations to test how population growth rate and ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Traditionally, fit matrix models represent the vast majority of demographic data available for comparative studies (e.g., those in the COMPADRE and COMADRE databases;Salguero-G omez et al 2015Salguero-G omez et al , 2016a or with which to assess the viability and management of species of conservation concern. Indeed, even as the accuracy of matrix models has been questioned, many synthetic reviews that reanalyze matrix models have recently appeared in the literature (Katz 2016, Csergo et al 2017, Yokomizo et al 2017). Thus, it is important to more carefully evaluate whether and when matrix models accurately capture population dynamics, and under what circumstances IPMs may do so with less bias and more precision.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, fit matrix models represent the vast majority of demographic data available for comparative studies (e.g., those in the COMPADRE and COMADRE databases;Salguero-G omez et al 2015Salguero-G omez et al , 2016a or with which to assess the viability and management of species of conservation concern. Indeed, even as the accuracy of matrix models has been questioned, many synthetic reviews that reanalyze matrix models have recently appeared in the literature (Katz 2016, Csergo et al 2017, Yokomizo et al 2017). Thus, it is important to more carefully evaluate whether and when matrix models accurately capture population dynamics, and under what circumstances IPMs may do so with less bias and more precision.…”
Section: Introductionmentioning
confidence: 99%
“…Our prediction that invasive populations of F. limosus would have greater maximum feeding rates than native populations was not supported, perhaps owing to an insufficient number of populations studied. There are numerous potential explanations for differences among per capita effects of populations, including differences in resident community composition (Barrios-O'Neill et al 2014;Médoc et al 2015;Wasserman et al 2016), time since invasion (Iacarella et al 2015a(Iacarella et al , 2015cYokomizo et al 2017;Evangelista et al 2019) and abiotic conditions (Eggleston 1990;Alexander et al 2012;Iacarella et al 2015b), but we were unable to determine the cause in our distributed experiments. In mesocosm experiments, Evangelista et al (2019) found contrasting ecological impacts amongst individuals from four invasive populations of red swamp crayfish (Procambarus clarkii) and thus demonstrated that even geographically-close populations can vary in intraspecific trait variability, consistent with studies showing trait differences amongst individuals across a single expanding population (e.g.…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, since λ 0 and dispersal distance together determine spread rate (see Skellam, 1951), our results shed further light on the role of demography as a key driver of spread in invasive plants (Coutts et al., 2011). Finally, our results can thus be used to develop optimal management strategies, which should be derived from population dynamics and their relationship with time since introduction (Yokomizo et al., 2017).…”
Section: Discussionmentioning
confidence: 99%